1993
DOI: 10.1080/00926239308404898
|View full text |Cite
|
Sign up to set email alerts
|

Sexual history and quality of current relationships in patients with obsessive compulsive disorder: A comparison with two other psychiatric samples

Abstract: It has been hypothesized that sexual conflict is a causal factor in the development of obsessive compulsive disorder. This study investigated the relationship between obsessive compulsive disorder and variables related to the individual's sexual history, present life, sexual satisfaction, and marital adjustment. Of inpatient admissions, 363 who met criteria for obsessive compulsive disorder, panic disorder, and depressive disorder completed a standard history questionnaire and the Marital Adjustment Test. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Feelings of anxiety are also a big part of OCD, which was found to be associated with sexual dissatisfaction and pain in our study. Only a handful of studies have reported on sexual function in obsessive patient populations, all of which suggest similar findings to ours [46,47].…”
Section: Discussionsupporting
confidence: 88%
“…Feelings of anxiety are also a big part of OCD, which was found to be associated with sexual dissatisfaction and pain in our study. Only a handful of studies have reported on sexual function in obsessive patient populations, all of which suggest similar findings to ours [46,47].…”
Section: Discussionsupporting
confidence: 88%
“…Inconsistent with the finding of Staebler, Pollard, and Merkel (1993) , however, we found that the sexual disjunction of OCD female patient was unique. Inconsistent with the finding of Staebler, Pollard, and Merkel (1993) , however, we found that the sexual disjunction of OCD female patient was unique.…”
Section: Discussionsupporting
confidence: 58%
“…Hoover and Insel (1984) speculate that obsessive compulsive individuals are prone to marital problems, perhaps because of a lack of sexual intimacy caused by the symptoms of obsessive compulsive disorder (OCD) . Staebler, Pollard, and Merkel (1993) reported that 60% of their obsessive compulsive sample reported sexual dissatisfaction with current partners. Staebler, Pollard, and Merkel (1993) reported that 60% of their obsessive compulsive sample reported sexual dissatisfaction with current partners.…”
mentioning
confidence: 99%
“…Family members are also frequently drawn into the ritualistic behaviors of OCD patients [12,14,15]. A few studies have shown that OCD is often associated with marital discord [16,17], inability to maintain relationships with others, especially friends [16], sexual problems [18], financial hardship [16,19], cutting down on family routines including leisure [19], and poor family relationships [20,21].…”
Section: Introductionmentioning
confidence: 99%